Identification of a large anguimorph lizard (Reptilia, Squamata) by an articulated hindlimb from the upper Maastrichtian (Upper Cretaceous) of Basturs-1 (Lleida, Spain). (March 2022) - Cabezuelo Hernández, A.; Bolet, A.; Torices, A.; Pérez-García, A.
Abstract: Appendicular remains of squamate reptiles are barely described in the fossil record due to their low preservational potential and generally poor diagnostic information. Not many squamate fossil individuals preserve appendicular bony elements, these being mainly restricted to the rare articulated specimens found in a limited number of localities with specific conditions that favor exceptional preservation. Detailed descriptions of these bones, especially tarsals and metatarsals, are thus scarce in the literature due to the lesser relevance given to these elements in most anatomical descriptions. In this study we analyze an unpublished fossil specimen from the Maastrichtian of Basturs-1 (Lleida, Catalonia, Spain) corresponding to several articulated appendicular pes bones of a possible member of Varaniformes. We also provide detailed insights on the anatomy of the tarsalia and metatarsalia, particularly in anguimorphs. The fossil specimen here described, with an estimated snout-vent length (SVL) of ∼581 mm, reveals the putative varaniform from Basturs-1 as one of the largest Mesozoic terrestrial lizards, and possibly the largest from the European fossil record. Previous observations of an association between large lizards and dinosaur nesting sites are further supported by the find of this giant form in a locality known for the presence of numerous dinosaur eggs. Highlights: A large anguimorph lizard has been identified in the Maastrichtian record of the Iberian Peninsula. It could be the largest terrestrial lizard from the European fossil record. This fossil specimen suggests the presence of Varaniformes in the Iberian Peninsula prior to the K-Pg limit.